Black phosphorus composite negative electrode material for sodium storage as well as preparation method and application of black phosphorus composite negative electrode material
By performing step-by-step ball milling of black phosphorus and sodium superion conductor Na3Zr2Si2PO12 and carbon nanotubes, a dense composite was formed, which solved the problems of low efficiency and poor circulation stability of black phosphorus composite materials in sodium ion batteries for the first time, and significantly improved the Electrochemical properties of sodium ion batteries.
Patent Information
- Application Number
- CN202411155412.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The existing black phosphorus composite anode material has low efficiency and poor circulation stability in sodium ion batteries, which limits the development and application of sodium ion batteries.
By performing step-by-step high-energy ball milling of black phosphorus with sodium superion conductor Na3Zr2Si2PO12 and carbon nanotubes, a dense composite is formed to form chemical bonds such as P-C, P-Na, P-Zr and P-Si, improving the structural stability and electronics of the material /ionic conductivity.
It significantly improves the first-time Coulomb efficiency and cycle stability of black phosphorus composite materials, improves the ratio capacity and electrochemical performance of sodium ion batteries, and solves the problem of low Coulomb efficiency for the first time.
Smart Images

Figure CN119230775A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a black phosphorus composite negative electrode material for sodium storage and a preparation method and application thereof, belonging to the technical field of new energy materials. Background Art
[0002] As a beneficial supplement to lithium-ion batteries, sodium-ion batteries have broad application prospects in low-speed or small and medium-sized passenger cars and energy storage fields. At present, hard carbon is the most mainstream choice for the negative electrode of sodium-ion batteries; however, hard carbon has problems such as low initial coulombic efficiency, poor rate performance, severe liquid absorption, unclear sodium storage mechanism, and poor safety, which will inevitably seriously hinder the in-depth development and application of sodium-ion battery technology. Therefore, it is very important to explore new negative electrode materials for sodium-ion batteries with excellent comprehensive performance.
[0003] Among many anode materials with practical prospects, black phosphorus (BP) has shown better advantages and potential, including: high electronic conductivity (300S m -1 ) is conducive to promoting its rate performance, and the alloy sodium storage mechanism gives it a high theoretical specific capacity (2596mAh g -1 ), suitable sodium storage potential (~0.4V vs Na + / Na) ensures its high safety. However, the practical application of BP in the field of sodium ion batteries is still greatly restricted by its low first coulombic efficiency and poor cycle stability. This is mainly due to the fact that when BP is sodiumized, it is easy to expose a fresh surface due to pulverization, which causes serious side reactions with the electrolyte, resulting in low coulombic efficiency. At the same time, the volume effect easily destroys the electron / ion mass transfer channel, causing the cycle stability to deteriorate. The preparation of BP composite materials by evaporation condensation and mechanical ball milling is the most commonly used method to improve its performance, among which the ball milling method with low cost and easy industrialization is more concerned. For example, the patent with publication number CN113437281A, ball-milled composite of black phosphorus, nano-graphite powder and nitrogen-doped carbon nanotubes, effectively improved the stability of black phosphorus composite negative electrode materials by constructing PC and POC bonds. For another example, the patent with publication number CN116826005A composites black phosphorus, β″-Al2O3 and acetylene black by ball milling, and by constructing chemical bonds such as PC, P-Al and POC, the black phosphorus composite negative electrode material has both good rate performance and cycle stability. Despite this, the technical methods disclosed so far have failed to overcome or improve the problem of low first coulombic efficiency of BP negative electrode. Therefore, how to develop a simple, easy, efficient and reliable new formula or new process based on ball milling to effectively improve the problem of low first coulombic efficiency of BP composite negative electrode is a key technical problem that needs to be solved to promote its development and application. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In order to solve the above problems in the prior art, the present invention provides a black phosphorus composite negative electrode material for sodium storage and a preparation method and application thereof, wherein the black phosphorus composite negative electrode material has a high first coulombic efficiency.
[0006] (II) Technical solution
[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0008] A black phosphorus composite negative electrode material for sodium storage, which is composed of black phosphorus, sodium superion conductor Na3Zr2Si2PO 12 (NZSP) and carbon nanotubes (CNTs), and black phosphorus is reacted with Na3Zr2Si2PO4 by mechanochemical reaction. 12 A dense composite is formed and the composite is interspersed with carbon nanotubes, and phosphorus-carbon (PC) bonds, phosphorus-sodium (P-Na) bonds, phosphorus-zirconium (P-Zr) bonds and phosphorus-silicon (P-Si) bonds are formed, wherein the black phosphorus, Na3Zr2Si2PO 12 The mass ratio of black phosphorus to Na3Zr2Si2PO 12 The mass ratio of the sum of the masses of the carbon nanotubes is 8-9:1-2.
[0009] As for the black phosphorus composite negative electrode material as described above, preferably, the particle size of the black phosphorus is micron-level or submicron-level, preferably 0.1-5 μm, wherein submicron-level refers to 0.1-1 μm, and micron-level refers to 1-5 μm.
[0010] As described above, the black phosphorus composite negative electrode material, preferably, the Na3Zr2Si2PO 12 The particle size is micron-sized, preferably 2 to 10 μm.
[0011] In the black phosphorus composite negative electrode material as described above, preferably, the carbon nanotubes are multi-walled carbon nanotubes, and the length thereof is 10 to 40 μm.
[0012] A method for preparing a black phosphorus composite negative electrode material for sodium storage comprises: sequentially reacting black phosphorus, a sodium superion conductor Na3Zr2Si2PO4 and a 12 (NZSP) and carbon nanotubes were synthesized by step-by-step high-energy ball milling.
[0013] In the preparation method as described above, preferably, the black phosphorus is micron-sized BP or block BP which is crushed by high-energy ball milling under the protection of an inert atmosphere and then sieved to obtain micron-sized BP;
[0014] Na3Zr2Si2PO 12The particle size is micrometer level; the carbon nanotubes are multi-walled carbon nanotubes, and the length is 10-40 μm. Furthermore, the sieve aperture used for sieving is 800-1600 mesh.
[0015] In the preparation method described above, preferably, the black phosphorus and Na3Zr2Si2PO 12 The black phosphorus and Na3Zr2Si2PO4 were first mixed and ball-milled in a mass ratio of 3-4:1-2. 12 The composite is ball-milled again with black phosphorus and carbon nanotubes in a mass ratio of 8-9:1-2.
[0016] In the preparation method as described above, preferably, the high-energy ball mill adopts a high-energy planetary ball mill, the ball-to-material ratio of ball mill beads is 10 to 60:1, the ball milling method is a unidirectional rotary ball mill, the ball milling speed is 600 to 800 rpm / min, and the ball milling time is 0.5 to 13 h.
[0017] Furthermore, black phosphorus and Na3Zr2Si2PO 12 The ball milling time of the first material is 6 to 13 hours; the ball milling time of the last three materials together is 0.5 to 1 hour.
[0018] A sodium ion battery, wherein the negative electrode of the sodium ion battery adopts the above-mentioned black phosphorus composite material or the black phosphorus composite material prepared by the above-mentioned preparation method.
[0019] (III) Beneficial effects
[0020] The beneficial effects of the present invention are:
[0021] The present invention provides a method for preparing a black phosphorus composite negative electrode material for sodium storage and its application. The composite negative electrode material is composed of black phosphorus (BP), carbon nanotubes (CNTs) and a sodium superion conductor Na3Zr2Si2PO4. 12 (NZSP) is obtained by step-by-step high-energy ball milling. After step-by-step ball milling, BP and NZSP form a dense complex and the complex is interspersed with CNTs, and chemical bonds such as PC, P-Na, P-Zr and P-Si are also formed. On the one hand, BP forms a dense physical contact with the auxiliary materials CNTs and NZSP. In particular, the densely structured ion conductor NZSP can effectively block the diffusion and penetration of the electrolyte and prevent the electrolyte from directly contacting BP to cause side reactions. At the same time, the sodium superion conductor can promote the migration of sodium ions and ensure the utilization of BP's rate capacity; on the other hand, chemical bonds such as PC, P-Na, P-Zr and P-Si can also effectively improve the stability of BP's sodium storage structure and alleviate volume expansion. These factors will jointly make BP-based composite materials used as negative electrodes for sodium-ion batteries have high first coulombic efficiency, better rate capacity and cycle stability, which effectively solves the technical problem of low first coulombic efficiency of black phosphorus negative electrode materials.
[0022] After a large number of experimental studies, it was found that there are three main types of existing technical solutions for preparing black phosphorus composite negative electrode materials by ball milling. The first is to use only electronic conductors (such as conductive carbon materials) and black phosphorus for ball milling to form chemical bonds such as PC; the second is to use electronic conductors and non-ionic conductors (such as titanium dioxide, sodium titanate, etc.) and black phosphorus for ball milling to form chemical bonds such as PC and P-Ti; the third is to use electronic conductors and ionic conductors (such as β″-Al2O3) and black phosphorus for ball milling to form chemical bonds such as PC and P-Al. Among them, the third type is the patent previously applied for by the inventor. Although the P-Al bond formed is bonded to the ionic conductor, it is significantly better than the P-Ti bond formed with the non-ionic conductor, and can significantly modify the ionic conductivity, thereby improving the rate performance, but cannot improve the disadvantages and shortcomings of the low first coulombic efficiency of black phosphorus-based composite negative electrode materials. The black phosphorus composite negative electrode material for sodium storage prepared by the present invention, that is, the BP / NZSP / CNTs composite material, solves the problem of low first coulombic efficiency. By observing the SEM photos of the product, it is found that it is due to the fact that NZSP is a dense ion conductor. In the prior art, that is, the previous patents did not consider the problem of the structural density of the ion conductor itself, or the word "density" did not appear, so it was impossible to give key inspiration, let alone predict. The present invention has found a composite material with a novel structure constructed by a step-by-step ball milling method, which solves the problem of low first coulombic efficiency. In particular, the solid electrolyte Na3Zr2Si2PO used 12 The sodium superionic conductor has an ionic conductivity comparable to that of β″-Al2O3; however, its microstructure is more compact, and this compact structural characteristic can effectively block the electrolyte, ensuring that the direct contact between BP and the electrolyte in the prepared composite negative electrode material is greatly reduced, so that the interfacial side reactions during the first discharge can be significantly reduced, thereby improving the first coulombic efficiency of the composite negative electrode. At the same time, the sodium superionic conductor NZSP has a richer elemental composition and can form a variety of chemical bonds with BP during high-energy ball milling, including: PC, P-Na, P-Zr and P-Si, etc. These chemical bonds improve the cyclic stability of black phosphorus-based composite materials better than β″-Al2O3 ionic conductors with less elemental composition. Therefore, the technical solution provided by the present invention is significantly progressive. In addition, step-by-step ball milling can effectively prevent the disadvantages and shortcomings of one-dimensional carbon nanotubes that are broken or fragmented in large quantities due to long-term ball milling, and cannot effectively improve the electronic conductivity of black phosphorus-based composite materials. Therefore, the BP / NZSP / CNTs composite negative electrode material prepared by the present invention also has an excellent three-dimensional electronic conductive network, which can effectively guarantee its rate capacity.
[0023] The black phosphorus composite negative electrode material for sodium storage provided by the present invention avoids the defects and shortcomings of using sodium-supplementing additives such as Na2C4O4, Na2CO3, and NaN3 to improve coulombic efficiency. Since the above-mentioned additives will inevitably produce harmful gases (such as CO2 or N2, etc.) during the circulation process, there are certain safety hazards.
[0024] The BP / NZSP / CNTs composite material prepared by the present invention has excellent first coulombic efficiency when used as the negative electrode of sodium ion battery. -1 and 1.0Ag -1 The first coulombic efficiency of the device exceeds 96% and can even approach 99%, which is significantly higher than that of existing technologies.
[0025] In the preparation method of the black phosphorus composite negative electrode material for sodium storage provided by the present invention, BP and Na3Zr2Si2PO 12 All can be micron-sized powders, while most existing technologies have requirements on the quality or size of black phosphorus or auxiliary materials, such as quantum dots, nanometers, etc., and meeting the above requirements usually requires higher technical costs. In addition, the CNTs used in the present invention are cheap industrial-grade multi-walled carbon nanotubes, and the carbon nanotubes do not need to be modified or complicatedly doped before use. Therefore, the preparation cost of the present invention is low, the investment cost is low, and it has good production benefits.
[0026] The preparation method of the invention has low cost, is easy to operate, has large batch output, stable product performance and wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The micron-sized black phosphorus powder obtained by ball milling and sieving in Example 1 (left), commercially available Na3Zr2Si2PO 12 (middle) and scanning electron microscope (SEM) images of industrial-grade carbon nanotubes (right);
[0028] Figure 2 This is the SEM image of the BP / NZSP / CNTs composite material prepared in Example 1;
[0029] Figure 3 The X-ray diffraction (XRD) pattern of the BP / NZSP / CNTs composite material prepared in Example 1;
[0030] Figure 4 P 2p high-resolution XPS spectra of BP (left), BP / CNTs composite material (middle) and BP / NZSP / CNTs composite material (right) prepared in Example 1;
[0031] Figure 5 The BP / NZSP / CNTs composite material prepared in Example 1 was used as the negative electrode of sodium ion battery at 0.1A g-1 Charge and discharge performance under current density;
[0032] Figure 6 The BP / NZSP / CNTs composite material prepared in Example 1 was used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0033] Figure 7 The BP / NZSP / CNTs composite material prepared in Example 2 was used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0034] Figure 8 The BP / NZSP / CNTs composite material obtained in Example 3 is used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0035] Fig. 9 The BP / NZSP / CNTs composite material obtained in Example 4 is used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0036] Fig.10 The BP / β″-Al2O3 / CNTs composite material prepared in Comparative Example 1 was used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle stability performance (B) under current density;
[0037] Fig.11 The BP / CNTs composite material prepared in Comparative Example 2 was used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0038] Fig.12 The BP / NZSP composite material prepared in Comparative Example 3 was used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0039] Fig.13 The RP / NZSP / CNTs composite material prepared in Comparative Example 4 was used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0040] Fig.14The BP / NZSP / CNTs composite material prepared by one-step ball milling in Comparative Example 5 was used as the negative electrode of sodium ion battery at 1.0A g -1 The charge and discharge performance (A) and cycle performance (B) diagram under current density;
[0041] Fig.15 The BP / NZSP / CNTs composite material prepared by dry mixing in a mixer in Comparative Example 6 was used as the negative electrode of a sodium ion battery at 1.0A g -1 Charge and discharge performance diagram under current density. DETAILED DESCRIPTION
[0042] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with the accompanying drawings through specific embodiments. The experimental methods in the following examples are conventional methods unless otherwise specified. The test materials used in the following examples are all commercially available products. Unless otherwise specified, the reagents are assumed to be directly purchased.
[0043] Example 1
[0044] A method and application of preparing a BP / NZSP / CNTs composite material using commercially available bulk black phosphorus, comprising the following steps:
[0045] (1) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 3 g of bulk black phosphorus and stainless steel ball milling beads were placed in a 50 mL stainless steel ball milling jar. The total mass of the stainless steel ball milling beads was 90 g, including 4 stainless steel ball milling beads with a diameter of 10 mm, 8 stainless steel ball milling beads with a diameter of 7 mm, and 25 stainless steel ball milling beads with a diameter of 3 mm. That is, the ball milling was performed at a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed was set to 600 rpm / min, the mode was unidirectional rotary ball milling, and the ball milling time was 6 h. After the ball milling, the obtained powder was sieved through an 800-mesh sieve to obtain micron-grade black phosphorus powder.
[0046] (2) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.75 g of the micron-sized black phosphorus powder obtained in step (1) and commercially available Na3Zr2Si2PO4 12 0.25 g of powder was placed in a 50 mL stainless steel ball mill. The total mass of the stainless steel ball mill beads was 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was carried out with a ball-to-material ratio of 30:1 (mass ratio). The ball mill speed was set to 600 rpm / min, and the ball milling time was 12 h. After the operation was completed, the BP / NZSP composite material was obtained.
[0047] (3) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.8 g of the BP / NZSP composite powder material obtained in step (2) and 0.2 g of industrial-grade carbon nanotube powder are placed in a 50 mL stainless steel ball mill jar, where the industrial-grade carbon nanotube powder is multi-walled carbon nanotubes with a length of 10 to 40 μm. The total mass of the stainless steel ball mill beads is 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling is performed at a ball-to-material ratio of 30:1 (mass ratio). The ball mill speed is set to 600 rpm / min, and the ball milling time is 1 h. After the operation is completed, the target product BP / NZSP / CNTs composite material is obtained.
[0048] The raw materials used were subjected to scanning electron microscopy. The results of SEM were as follows: Figure 1 As shown in the figure, the left side is the micron-sized black phosphorus powder obtained by sieving the ball-milled black phosphorus block, and the middle is the commercially available Na3Zr2Si2PO 12 , the right side is industrial-grade carbon nanotubes, the scale in the figure is 1μm. It can be seen from the figure that black phosphorus is irregular particles of micron or submicron size, Na3Zr2Si2PO 12 It is a dense block structure composed of submicron particles, and carbon nanotubes are a one-dimensional fibrous structure.
[0049] The obtained BP / NZSP / CNTs composite material was tested by scanning electron microscopy. Figure 2 The SEM image of the BP / NZSP / CNTs composite material shows the black phosphorus and Na3Zr2Si2PO4 after ball milling. 12 They are uniformly mixed together to form a dense complex of larger size, and the complex is interspersed with carbon nanotubes.
[0050] The obtained BP / NZSP / CNTs composite material was subjected to X-ray diffraction test. The results are as follows Figure 3 The XRD spectrum of the BP / NZSP / CNTs composite material is shown in Figure 2. By comparing the XRD spectrum of the single phase, it can be seen that the various phases in the composite material after ball milling have a tendency to become amorphous, but Na3Zr2Si2PO 12 The phase still has clear and sharp diffraction peaks, suggesting its excellent structural stability.
[0051] Figure 4 P 2p high-resolution XPS spectra of the above-mentioned BP, BP / CNTs composites and BP / NZSP / CNTs composites. The results confirm the existence of PC bonds, P-Na bonds, P-Zr bonds and P-Si bonds in the BP / NZSP / CNTs composite samples.
[0052] Electrochemical performance test:
[0053] The composite material prepared above is used for the negative electrode of sodium ion battery. BP / NZSP / CNTs composite material (active material), acetylene black (conductive agent), sodium carboxymethyl cellulose and styrene butadiene rubber (binder) are mixed in a mass ratio of 85:5:3:7 with water as solvent and then coated on aluminum foil with a coating thickness of 20 to 100 μm. After vacuum drying and cutting, electrode sheets are made. Battery assembly and performance test method:
[0054] The CR2025 button cell was assembled in an argon glove box with a water and oxygen content of less than 0.01 mg / L. The prepared dry electrode sheet was transferred to the glove box, matched with the metal sodium sheet (counter electrode and reference electrode), separated by a glass fiber membrane, and a few drops of 1M NaPF6 dissolved in DMC:EC:EMC (volume ratio of 1:1:1) electrolyte solution containing 5wt% FEC additive were added; finally, the battery was sealed and left to stand for 6 hours. The rested battery was placed in the Xinwei battery testing system for testing, where: the charge and discharge cut-off voltage window was set to 0.01V~2.5V; the charge and discharge were carried out in a constant current mode, and the current density was set to 0.1Ag. -1 and 1.0Ag -1 The experimental results can be found in Figure 5 and Figure 6 shown.
[0055] like Figure 5 As shown, at 0.1Ag -1 The charge and discharge curve under the current density is about 1630.5 mAh g -1 The first charge capacity is about 1651.2mAh g -1 , the first Coulombic efficiency reached 98.7%.
[0056] like Figure 6 As shown, at 1.0Ag -1 The charge and discharge curve under the current density is about 1479.6 mAh g -1 The first charge capacity is about 1433.7mAh g -1 The first coulombic efficiency was as high as 96.9%. The cycle stability of the composite material was further tested, and the test results showed that the reversible capacity of the 1st, 2nd and 100th cycles was 1479.6 mAh g -1 、1434.3mAh g -1 and 1334.6mAh g -1 The capacity retention rate after 100 cycles is as high as 90.2%, showing excellent rate capacity and cycle stability.
[0057] Example 2
[0058] A method and application of preparing a BP / NZSP / CNTs composite material using commercially available powdered black phosphorus, comprising the following steps:
[0059] (1) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.75 g of sieved commercially available micron-sized (1-5 μm) powdered black phosphorus and commercially available Na3Zr2Si2PO4 were added to the mixture. 12 0.25 g of powder was placed in a 50 mL stainless steel ball mill. The total mass of the stainless steel ball mill beads was 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was carried out with a ball-to-material ratio of 30:1 (mass ratio). The ball mill speed was set to 600 rpm / min, and the ball milling time was 12 h. After the operation was completed, the BP / NZSP composite material was obtained.
[0060] (2) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.8 g of the BP / NZSP composite material powder obtained in step (1) and 0.2 g of industrial-grade carbon nanotube powder were placed in a 50 mL stainless steel ball mill, where the total mass of the stainless steel ball mill beads was 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was performed at a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed was set to 600 rpm / min, and the ball milling time was 1 h. After the operation was completed, the target product BP / NZSP / CNTs composite material was obtained.
[0061] Electrochemical performance test:
[0062] The electrode sheet production, battery assembly and performance testing methods are the same as those in Example 1. The performance test results are shown in Figure 7 Shown: At 1.0Ag -1 The charge and discharge curve under the current density is about 1424.5 mAh g -1 The first charge capacity is about 1375.5mAh g -1 The first coulombic efficiency is as high as 96.5%; in addition, the reversible capacities of the 1st, 2nd and 100th cycles are 1424.5 mAh g -1 、1392.4mAh g -1 and 1270.2mAh g -1 , similar to Example 1, with excellent rate capacity and cycle stability.
[0063] Example 3
[0064] A method and application of preparing BP / NZSP / CNTs composite material in a single tank, comprising the following steps:
[0065] (1) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 5 g of bulk black phosphorus and stainless steel ball milling beads were placed in a 50 mL stainless steel ball milling jar. The total mass of the stainless steel ball milling beads was 100 g, including 10 stainless steel ball milling beads with a diameter of 10 mm, 20 stainless steel ball milling beads with a diameter of 7 mm, and 80 stainless steel ball milling beads with a diameter of 3 mm. That is, the ball-to-material ratio was 20:1 (mass ratio) and the ball milling speed was set to 800 rpm / min. The specific operation mode was unidirectional rotary ball milling, and the ball milling time was 2 h. After the ball milling, the obtained powder was sieved through an 800-mesh sieve to obtain black phosphorus powder with a particle size of 0.1 to 5 μm.
[0066] (2) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 3.75 g of the micron-sized black phosphorus powder obtained in step (1) and commercially available Na3Zr2Si2PO4 12 1.25 g of powder was placed in a 50 mL stainless steel ball mill jar. The total mass of the stainless steel ball mill beads was 250 g, including 12 stainless steel ball mill beads with a diameter of 10 mm, 30 stainless steel ball mill beads with a diameter of 7 mm, and 120 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was carried out with a ball-to-material ratio of 50:1 (mass ratio). The ball mill speed was set to 600 rpm / min, the ball milling time was 12 h, and the BP / NZSP composite material was obtained after the operation was completed.
[0067] (3) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 4 g of the BP / NZSP composite powder material obtained in step (2) and 1 g of industrial-grade carbon nanotube powder were placed in a 50 mL stainless steel ball mill. The total mass of the stainless steel ball mill beads was 200 g, including 12 stainless steel ball mill beads with a diameter of 10 mm, 25 stainless steel ball mill beads with a diameter of 7 mm, and 100 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was performed with a ball-to-material ratio of 40:1 (mass ratio). The ball mill speed was set to 600 rpm / min, and the ball milling time was 2 h. After the operation was completed, 5 g of the target product BP / NZSP / CNTs composite material was obtained.
[0068] Electrochemical performance test:
[0069] The electrode sheet production, battery assembly and performance testing methods are the same as those in Example 1. The performance test results are shown in Figure 8 Shown: At 1.0Ag -1 The charge and discharge curve under the current density is about 1443.9 mAh g -1 The first charge capacity is about 1386.4mAh g -1The first coulombic efficiency is as high as 96.0%; in addition, the reversible capacities of the 1st, 2nd and 100th cycles are 1443.9 mAh g -1 、1406.8mAh g -1 and 1282.2mAh g -1 , similar to Example 1, with excellent rate capacity and cycle stability.
[0070] Example 4
[0071] A method and application of preparing BP / NZSP / CNTs composite material in a single tank, comprising the following steps:
[0072] (1) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 10 g of bulk black phosphorus and stainless steel ball milling beads were placed in a 50 mL stainless steel ball milling jar. The total mass of the stainless steel ball milling beads was 200 g, including 12 stainless steel ball milling beads with a diameter of 10 mm, 25 stainless steel ball milling beads with a diameter of 7 mm, and 100 stainless steel ball milling beads with a diameter of 3 mm. That is, the ball-to-material ratio was 20:1 (mass ratio). The ball milling speed was set to 800 rpm / min. The specific operation mode was unidirectional rotary ball milling, and the ball milling time was 2 h. After the ball milling was completed, the obtained powder was sieved through an 800-mesh sieve to obtain black phosphorus powder with a particle size of 0.1 to 5 μm.
[0073] (2) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 7.5 g of the micron-sized black phosphorus powder obtained in step (1) and commercially available Na3Zr2Si2PO4 12 2.5 g of powder was placed in a 50 mL stainless steel ball mill jar. The total mass of the stainless steel ball mill beads was 200 g, including 12 stainless steel ball mill beads with a diameter of 10 mm, 25 stainless steel ball mill beads with a diameter of 7 mm, and 100 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was carried out with a ball-to-material ratio of 20:1 (mass ratio). The ball mill speed was set to 600 rpm / min, the ball milling time was 6 h, and the BP / NZSP composite material was obtained after the operation was completed.
[0074] (3) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 8 g of the BP / NZSP composite powder material obtained in step (2) and 2 g of industrial-grade carbon nanotube powder were placed in a 50 mL stainless steel ball mill. The total mass of the stainless steel ball mill beads was 200 g, including 12 stainless steel ball mill beads with a diameter of 10 mm, 25 stainless steel ball mill beads with a diameter of 7 mm, and 100 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was performed with a ball-to-material ratio of 20:1 (mass ratio). The ball milling speed was set to 800 rpm / min, and the ball milling time was 0.5 h. After the operation was completed, 10 g of the target product BP / NZSP / CNTs composite material was obtained.
[0075] Electrochemical performance test:
[0076] The electrode sheet production, battery assembly and performance testing methods are the same as those in Example 1. The performance test results are shown in Fig. 9 Shown: At 1.0Ag -1 The charge and discharge curve under the current density is about 1451.5 mAh g -1 The first charge capacity is about 1397.1mAh g -1 The first coulombic efficiency is as high as 96.3%; in addition, the reversible capacities of the 1st, 2nd and 100th cycles are 1451.5 mAh g -1 、1385.5mAh g -1 and 1223.9mAh g -1 , similar to Example 1, with excellent rate capacity and cycle stability.
[0077] Through the above examples, it can be concluded that the preparation method of the BP / NZSP / CNTs composite material provided by the present invention is low-cost, easy to operate, has a large batch output, stable product performance, and has wide applicability. In particular, the BP / NZ SP / CNTs composite material used as the negative electrode of a sodium ion battery has an extremely high first coulomb efficiency and better rate capacity and cycle stability. In addition, the technical method does not have strict requirements on the quality of black phosphorus, and the use of micron-level black phosphorus with relatively low process and cost can achieve the expected purpose and effect, indicating that the technology of the present invention has better application prospects and potential.
[0078] Comparative Example 1
[0079] A method and application of preparing BP / β″-Al2O3 / CNTs composite material using commercially available bulk black phosphorus, comprising the following steps:
[0080] (1) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 3 g of bulk black phosphorus and stainless steel ball milling beads were placed in a 50 mL stainless steel ball milling jar. The total mass of the stainless steel ball milling beads was 90 g, including 4 stainless steel ball milling beads with a diameter of 10 mm, 8 stainless steel ball milling beads with a diameter of 7 mm, and 25 stainless steel ball milling beads with a diameter of 3 mm. The ball milling was performed at a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed was set to 600 rpm / min, the mode was unidirectional rotary ball milling, and the ball milling time was 6 h. After the ball milling, the obtained powder was sieved through an 800-mesh sieve to obtain micron-grade black phosphorus powder.
[0081] (2) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.75 g of the micron-sized black phosphorus powder obtained in step (1) and 0.25 g of commercially available micron-sized β″-Al2O3 powder were placed in a 50 mL stainless steel ball mill, where the total mass of the stainless steel ball mill beads was 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was performed at a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed was set to 600 rpm / min, and the ball milling time was 12 h. After the operation was completed, a BP / β″-Al2O3 composite material was obtained.
[0082] (3) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.8 g of the BP / β″-Al2O3 composite powder material obtained in step (2) and 0.2 g of industrial-grade carbon nanotube powder are placed in a 50 mL stainless steel ball mill, where the total mass of the stainless steel ball mill beads is 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling is performed at a ball-to-material ratio of 30:1 (mass ratio). The ball mill speed is set to 600 rpm / min, and the ball milling time is 1 h. After the operation is completed, the target product BP / β″-Al2O3 / CNTs composite material is obtained.
[0083] Electrochemical performance test:
[0084] The electrode sheet production, battery assembly and performance testing methods are the same as those in Example 1. The performance test results are shown in Fig.10 Shown: At 1.0Ag -1 The charge and discharge curve under the current density is about 1319.3 mAh g -1 The first charge capacity is about 1178.1mAh g -1 The initial coulombic efficiency is as high as 89.3%. In addition, the reversible capacities of the 1st, 2nd and 100th cycles are 1319.2 mAh g -1 , 1193.9mAh g -1 and 1017.2mAh g -1 , the capacity retention rate after 100 cycles is only 78.2%.
[0085] Comparative Example 1 proves that, using the same process, if β″-Al2O3 is added, the excellent first coulombic efficiency, rate capacity and cycle stability of the embodiment of the present invention cannot be achieved, indicating that the element-rich and densely structured Na3Zr2Si2PO 12 Compared with relatively single-element, non-dense β″-Al2O3 ion conductors, ion conductors are more helpful in improving the comprehensive sodium storage performance of black phosphorus-based composite materials.
[0086] Comparative Example 2
[0087] A method and application of preparing BP / CNTs composite material using commercially available bulk black phosphorus, comprising the following steps:
[0088] (1) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 3 g of bulk black phosphorus and stainless steel ball milling beads were placed in a 50 mL stainless steel ball milling jar. The total mass of the stainless steel ball milling beads was 90 g, including 4 stainless steel ball milling beads with a diameter of 10 mm, 8 stainless steel ball milling beads with a diameter of 7 mm, and 25 stainless steel ball milling beads with a diameter of 3 mm. The ball milling was performed at a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed was set to 600 rpm / min, the mode was unidirectional rotary ball milling, and the ball milling time was 6 h. After the ball milling, the obtained powder was sieved through an 800-mesh sieve to obtain micron-grade black phosphorus powder.
[0089] (2) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.6 g of the micron-sized black phosphorus powder obtained in step (1) and 0.4 g of the industrial-grade carbon nanotube powder are placed in a 50 mL stainless steel ball mill, where the total mass of the stainless steel ball mill beads is 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling is performed at a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed is set to 600 rpm / min, and the ball milling time is 1 h. After the operation is completed, the target product BP / CNTs composite material is obtained.
[0090] Electrochemical performance test:
[0091] The electrode sheet production, battery assembly and performance testing methods are the same as those in Example 1. The performance test results are shown in Fig.11 Shown: At 1.0Ag -1 The charge and discharge curve under the current density is about 951.2 mAh g -1 The first charge capacity is about 818.0mAh g -1 The first coulombic efficiency is 85.9%; in addition, the reversible capacities of the 1st, 2nd and 100th cycles are 951.2 mAh g -1 、826.9mAh g -1 and 714.8mAh g -1 .
[0092] Comparative Example 3
[0093] A method and application of preparing a BP / NZSP composite material using commercially available bulk black phosphorus, comprising the following steps:
[0094] (1) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 3 g of bulk black phosphorus and stainless steel ball milling beads were placed in a 50 mL stainless steel ball milling jar. The total mass of the stainless steel ball milling beads was 90 g, including 4 stainless steel ball milling beads with a diameter of 10 mm, 8 stainless steel ball milling beads with a diameter of 7 mm, and 25 stainless steel ball milling beads with a diameter of 3 mm. The ball milling was performed at a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed was set to 600 rpm / min, the mode was unidirectional rotary ball milling, and the ball milling time was 6 h. After the ball milling, the obtained powder was sieved through an 800-mesh sieve to obtain micron-grade black phosphorus powder.
[0095] (2) In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.6 g of the micron-sized black phosphorus powder obtained in step (1) and commercially available Na3Zr2Si2PO4 12 0.4 g of powder was placed in a 50 mL stainless steel ball mill jar. The total mass of the stainless steel ball mill beads was 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was carried out with a ball-to-material ratio of 30:1 (mass ratio). The ball mill speed was set to 600 rpm / min, and the ball milling time was 12 h. After the operation was completed, the BP / NZSP composite material was obtained.
[0096] Electrochemical performance test:
[0097] The electrode sheet production, battery assembly and performance testing methods are the same as those in Example 1. The performance test results are shown in Fig.12 Shown: At 1.0Ag -1 The charge and discharge curve under the current density is about 1032.1 mAh g -1 The first charge capacity is about 954mAh g -1 The first coulombic efficiency is 92.4%; in addition, the reversible capacities of the 1st, 2nd and 100th cycles are 1032.1 mAh g -1 , 948.7mAh g -1 and 946.4mAh g -1 .
[0098] Comparative Examples 2 and 3 show that, using the same process, if Na3Zr2Si2PO4 is not added, 12 or carbon nanotubes, all of which cannot achieve the excellent first coulombic efficiency, rate capacity and cycle stability of the embodiments of the present invention. In other words, the Na3Zr2Si2PO 12The ball-milled composite of carbon nanotubes and black phosphorus has a synergistic effect, that is, compared with BP / NZSP composite materials or BP / CNTs composite materials, BP / NZSP / CNTs composite materials have a more excellent electronic / ionic conductive network, rich surface chemical bonds, and can effectively block the penetration of electrolyte, so they show better comprehensive sodium storage performance.
[0099] Comparative Example 4
[0100] This comparative example is based on Example 1, except that the black phosphorus in Example 1 is replaced by red phosphorus (RP), and the other methods remain unchanged.
[0101] Fig.13 The prepared RP / NZSP / CNTs composite material was used as the negative electrode for sodium ion batteries at 1.0A g -1 The charge-discharge curve and cycle stability under current density are shown in Table 1. The first discharge capacity is about 1005.6 mAh g -1 The first charge capacity is about 938.9mAh g -1 The initial coulombic efficiency is 93.4%; in addition, the reversible capacities at the 1st, 2nd and 100th cycles are 1005.6 mAh g -1 、943.2mAh g -1 and 796.6mAh g -1 .
[0102] This comparative example proves that black phosphorus is a high-performance sodium storage negative electrode material with more advantages and potential than red phosphorus. Because of this, the present invention uses black phosphorus as the main body instead of red phosphorus. In the final analysis, there are mainly the following reasons: first, black phosphorus is the most stable among allotropes of phosphorus, while red phosphorus is prone to phase transformation during use or modification; second, black phosphorus presents a warped atomic layer, and the interlayers are stacked into a graphite-like structure through van der Waals forces, which is more conducive to sodium ion storage than red phosphorus; third, the electronic conductivity of black phosphorus is as high as 10 2 S m -1 , much higher than red phosphorus (~10 -14 S cm -1 ).
[0103] Comparative Example 5
[0104] A method and application of preparing a BP / NZSP / CNTs composite material using commercially available powdered black phosphorus, comprising the following steps:
[0105] In an argon glove box with a water and oxygen content of less than 0.1 mg / L, 0.6 g of sieved commercially available micron-sized (1-5 μm) powdered black phosphorus and 0.6 g of commercially available Na3Zr2Si2PO4 were added. 120.2 g of powder and 0.2 g of industrial-grade carbon nanotube powder were placed in a 50 mL stainless steel ball mill. The total mass of the stainless steel ball mill beads was 30 g, including 2 stainless steel ball mill beads with a diameter of 10 mm, 5 stainless steel ball mill beads with a diameter of 7 mm, and 12 stainless steel ball mill beads with a diameter of 3 mm. That is, unidirectional rotary ball milling was carried out with a ball-to-material ratio of 30:1 (mass ratio). The ball milling speed was set to 600 rpm / min, the ball milling time was 12 h, and the BP / NZSP / CNTs composite material was obtained after the operation was completed.
[0106] Electrochemical performance test:
[0107] The electrode sheet production, battery assembly and performance testing methods are the same as those in Example 1. The performance test results are shown in Fig.14 Shown: At 1.0Ag -1 The charge and discharge curve under the current density is about 1429.56 mAh g -1 The first charge capacity is about 1315.22mAh g -1 The first coulombic efficiency is about 92.0%; in addition, the reversible capacities of the 1st, 2nd and 100th cycles are 1429.56 mAh g -1 , 1318.35mAh g -1 and 1043.59mAh g -1 .
[0108] Comparative Example 6
[0109] This comparative example is based on Example 1. The micron-sized black phosphorus powder prepared according to step (1) of Example 1 and the commercially available Na3Zr2Si2PO4 12 The powder is mixed with industrial-grade carbon nanotube powder by dry stirring in a mixer, and then the obtained material is mixed with acetylene black (conductive agent), sodium carboxymethyl cellulose and styrene-butadiene rubber (binder) in a mass ratio of 85:5:3:7 and evenly coated on aluminum foil, and then vacuum dried and cut to make electrode sheets. The sodium ion battery assembly and performance test method are the same as in Example 1.
[0110] Fig.15 In this comparative example, a BP / NZSP / CNTs composite material was prepared by dry mixing in a mixer for use as a negative electrode for a sodium ion battery. -1 The charge and discharge curve under the current density is about 908.4 mAh g -1 The first charge capacity is about 521.8 mAh g -1 , the first Coulombic efficiency was only 57.4%, and the subsequent reversible capacity rapidly decayed to a negligible level.
[0111] In the preparation method provided by the present invention, the sodium superion conductor Na3Zr2Si2PO 12 After step-by-step ball milling, the electron conductor carbon nanotubes and micron-sized black phosphorus form a dense composite, which also contains a three-dimensional conductive network of electrons and ions and a large number of rich chemical bonds, thereby effectively improving the comprehensive sodium storage performance of the composite material. However, in comparative example 5, the one-step ball milling is used. During the long-term ball milling process, the carbon nanotubes are easily broken into fine fragments, which then destroys the structural advantages of the one-dimensional electronic conductive network of the carbon nanotubes, resulting in poor electrochemical performance of the prepared composite negative electrode; in particular, comparative example 6 adopts a direct mixing method, which cannot form a dense physical contact, let alone a surface chemical bond, so the sodium storage performance is far inferior to that of Example 1.
[0112] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A black phosphorus composite negative electrode material for sodium storage, characterized in that: It is composed of black phosphorus, sodium superion conductor Na3Zr2Si2PO 12 and carbon nanotubes, and the mechanochemical reaction between black phosphorus and Na3Zr2Si2PO 12 A dense composite is formed and the composite is interspersed with carbon nanotubes, and phosphorus-carbon bonds, phosphorus-sodium bonds, phosphorus-zirconium bonds and phosphorus-silicon bonds are formed. The black phosphorus, Na3Zr2Si2PO 12 The mass ratio of black phosphorus to Na3Zr2Si2PO 12 The mass ratio of the sum of the masses of the carbon nanotubes is 8-9:1-2.
2. The black phosphorus composite negative electrode material according to claim 1, characterized in that: The particle size of the black phosphorus is micron or submicron, Na3Zr2Si2PO 12 The particle size is micron level.
3. The black phosphorus composite negative electrode material according to claim 1, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with a length of 10 to 40 μm.
4. A method for preparing a black phosphorus composite negative electrode material for sodium storage, characterized in that: The method includes sequentially reacting black phosphorus, sodium superion conductor Na3Zr2Si2PO4 and 12 (NZSP) and carbon nanotubes were synthesized by step-by-step high-energy ball milling.
5. The preparation method according to claim 4, characterized in that: The black phosphorus is micron-level or submicron-level BP or block BP which is crushed by high-energy ball milling under the protection of inert atmosphere and then sieved to obtain micron-level BP. Na3Zr2Si2PO 12 The particle size is micron-level; the carbon nanotubes are multi-walled carbon nanotubes with a length of 10 to 40 μm.
6. The preparation method according to claim 5, characterized in that: The sieve aperture used for screening is 800 to 1600 mesh.
7. The preparation method according to claim 4, characterized in that: The black phosphorus and Na3Zr2Si2PO 12 The black phosphorus and Na3Zr2Si2PO4 were first mixed and ball-milled in a mass ratio of 3-4:1-2. 12 The composite is ball-milled again with black phosphorus and carbon nanotubes in a mass ratio of 8-9:1-2.
8. The preparation method according to claim 4, characterized in that: The high-energy ball mill adopts a high-energy planetary ball mill, the ball-to-material ratio of the ball milling beads is 10-60:1, the ball milling method is a unidirectional rotary ball mill, the ball milling speed is 600-800rpm / min, and the ball milling time is 0.5-13h.
9. The preparation method according to claim 1, characterized in that: Black phosphorus and Na3Zr2Si2PO 12 The ball milling time of the first material is 6 to 13 hours; the ball milling time of the last three materials together is 0.5 to 1 hour.
10. A sodium ion battery, wherein the negative electrode of the sodium ion battery is the black phosphorus composite negative electrode material according to any one of claims 1 to 3 or the black phosphorus composite negative electrode material prepared by the preparation method according to any one of claims 4 to 9.
Citation Information
Patent Citations
Method for simply preparing Na3Zr2PSi2O12 powder serving as sodium super ion conductor
CN110797570A
Application of red phosphorus / carbon nanotube composite material in sodium ion capacitor
CN113745011A
Black phosphorus composite material for negative electrode of sodium-ion battery as well as preparation method and application of black phosphorus composite material
CN116826005A
NASICON type fast ion conductor nanofiber and preparation method thereof
CN117317356A
Sodium-ion battery negative electrode material and preparation method and application thereof
CN117913249A